The Role of Financial Technology in Achieving Sustainable Development: A Case Study on Blockchain Implementation in the Financial Sector. (Sebha University Conference Proceedings, 2024)
This study aims to understand how blockchain technology can contribute to achieving sustainable development goals in the financial sector. This includes analyzing the impact of blockchain on financial operations, identifying challenges and opportunities arising from its adoption, and evaluating its effect on transparency and accountability in the financial sector. A case study was also conducted to understand how sustainable development can be achieved through the adoption of this technology. The study followed a descriptive approach to answer the research problem. In the theoretical section, the concept of blockchain technology and its importance were clarified, along with the significance of sustainable development. In the practical section, an exploratory study method was used on a sample of commercial banks to illustrate the relationship between financial technology (blockchain technology) and sustainable development through the collection, analysis, and interpretation of data and statistics used. The study included a sample of 48 employees working at Commercial Bank and Development Bank, and Al Wahda Bank, given the presence of their main offices in Benghazi city. Forty questionnaire forms were selected for statistical analysis, representing 83% of the total sample, which is a reasonable and acceptable percentage for conducting the study.Data were collected using a questionnaire distributed to the target sample. The SPSS program was used to enter and analyze the data and achieve the set objectives within the research framework. The researcher used appropriate statistical methods for data analysis, such as weighted arithmetic means, standard deviations, coefficients of variation, and percentage weights. The reliability and validity of the questionnaire were measured using Cronbach's alpha to test the credibility and reliability of the responses. The researcher employed the five-point Likert scale to measure responses.